Growth and Bioremediation properties of Oyster mushroom (Pleurotus ostreatus) using gold and bauxite mining soils in Guyana - Jaikaran, Sahsha; Ansari, Abdullah Adil; Seecharran, Diana (Mushroom Research, 2017)
This project endeavored to determine the growth and heavy metal content of the fruiting bodies of Pleurotusostreatus (oyster mushroom) grown in substrate containing rice straw, vermi-soil, calcium carbonate and soil from a gold mining area or a bauxite mining are in Guyana. The concentrations of Co, Pb, Cu, Fe and Mn in the samples were determined by Dry Ashing and Atomic Absorption (AA) spectrometry. The results indicate that the growth of P. ostreatus was observed to be significantly greater in gold mining soil versus bauxite mining soil. In addition, P. ostreatus showed the potentially to bio-accumulate heavy metals in its fruiting bodies in bothÂ gold and bauxite mining soils, however the quantity of heavy metals that were bioaccumulated did not prove to be a significant amount.